(untitled) (Al-Qamar, 2021)
In International Politics and International Relations, it is verified that neighbouring countries always affect each other. In this article we investigated the role of Afghan political culture in the insecurity of Afghanistan as well as Pakistan. Most of the countries considered Pakistan as a sponsor of terrorism in Afghanistan. But this study analysed that Pakistan is a victim of terrorism due to the political culture of Afghanistan. Afghan people obey a set of laws called Pakhtunwali. According to one of its law, they provide shelter to anybody who requests them for it. So that some terrorist organizations use this law and succeeded to get safe place in the country. This took the country into the chaos. Afghanistan has been encountering civil disintegration for many decades. On the other hand Pakistani and Afghan people have close relations to each other. So Pakistan is also affected by the chaos in Afghanistan. Although Pakistan has been alleged as a terrorist country by its rival neighbour India throughout their post-independence history, but this is Afghan relations which make Pakistan notorious in all over the world.